Five-Feature Model for Developing the Classifier for Synergistic vs. Antagonistic Drug Combinations Built by XGBoost - Ji, Xiangjun; Tong, Weida; Liu, Zhichao; Shi, Tieliu (Frontiers in Genetics, 2019)
Combinatorial drug therapy can improve the therapeutic effect and reduce the corresponding adverse events. In silico strategies to classify synergistic vs antagonistic drug pairs is more efficient than experimental strategies. However, most of the developed methods have been applied only to cancer therapies. In this study, we introduce a novel method, XGBoost, based on five features of drugs and biomolecular networks of their targets, to classify synergistic vs antagonistic drug combinations from different drug categories. We found that XGBoost outperformed other classifiers in both stratified 5-fold cross-validation and independent validation. For example, XGBoost achieved higher predictive accuracy than other models (0.86, 0.78, 0.78 and 0.83 for XGBoost, logistic regression, naïve Bayesian, and random forest, respectively) for an independent validation set. We also found that the five-feature XGBoost model is much more effective at predicting combinatorial therapies that have synergistic effects than those with antagonistic effects. The five-feature XGBoost model was also validated on TCGA data with accuracy of 0.79 among the 61 tested drug pairs, which is comparable to that of DeepSynergy. Among the 14 main anatomical/pharmacological groups classified according to WHO Anatomic Therapeutic Class, for drugs belonging to five groups, their prediction accuracy was significantly increased (odds ratio < 1) or reduced (odds ratio > 1) (Fisher’s exact test, p < 0.05). This study concludes that our five-feature XGBoost model has significant benefits for classifying synergistic vs antagonistic drug combinations.